Membuka Formula Keberhasilan Belajar: Kemandirian, Motivasi, dan Dukungan Sosial Sebagai Kunci Untuk Hasil Yang Cemerlang (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This research aims to determine the influence of learning independence, learning motivation and social support on the learning outcomes of Office Administration Education Students for the 2020/2021 Academic Year, Jakarta State University. The population in this study were Office Administration Education Students for the 2020/2021 Academic Year, Jakarta State University. The research sample was taken from 101 respondents. The research method used is quantitative. SmartPLS (Partial Least Squares) is used to calculate data analysis in this research. The Outer Model includes Convergent Reability, Discriminant Validity, Composite Reability, and Cronbach's Alpha calculations, while the Inner Model includes T-statistics, R-Squares, F-Squares, and VIF calculations. The findings of this research state that: 1) learning independence has a positive and significant influence on learning outcomes, 2) learning motivation has a positive and significant influence on learning outcomes, 3) social support has a positive and significant influence on learning outcomes, 4) learning independence , learning motivation and social support simultaneously influence the learning outcomes of students in the Office Administration Education Study Program for the 2020/2021 Academic Year, Jakarta State University.